Sporadic inclusion body myositis: Phenotypic variability and influence of HLA-DR3 in a cohort of 57 Australian cases. Issue 9 (7th February 2008) - Needham, M; James, I; Corbett, A; Day, T; Christiansen, F; Phillips, B; Mastaglia, F L
Abstract : Background and Aims: There have been few studies of the variability in the clinical phenotype in sporadic inclusion body myositis (sIBM) and it is not known whether the human leucocyte antigen (HLA) haplotype influences the phenotype and course of the disease. We studied a large cohort of patients with sIBM in order to determine the degree of phenotypic variability and different modes of presentation, as well as the influence of HLA haplotypes. Method: A cross-sectional study of 57 biopsy-proven sIBM cases from three Australian centres was performed. Patients were interviewed and examined by a single investigator, and had HLA typing and autoantibody studies. Results: Although the initial symptoms in the majority of cases were attributable to quadriceps weakness (79%), a proportion of patients presented due to finger weakness (12%), foot drop (7%) or dysphagia (1.8%). Although the majority had the classic combination of quadriceps and forearm muscle involvement, some patients had predominantly forearm weakness with sparing of the quadriceps, or severe involvement of the anterior tibial muscles. Asymmetrical involvement was common (82%), particularly of the forearm muscles, with the non-dominant side being more severely affected in most cases. Carriage of the HLA-DRB1*0301 (DR3) allele was associated with lower quadriceps muscle strength and a more rapid decline in strength. Conclusions: The findings emphasise the variability in the mode of presentation, patterns of muscle involvement and clinical course of sIBM in this population, and indicate that the HLA-DRB1*0301 (DR3) allele may influence the rate of progression as well as susceptibility to the disease.